2009
DOI: 10.1088/0964-1726/18/12/125011
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive model for piezoceramic actuators: modelling, validation and application

Abstract: This paper presents a comprehensive model for piezoceramic actuators (PAs), which accounts for hysteresis, non-linear electric field and dynamic effects. The hysteresis model is based on the widely used general Maxwell slip model, while an enhanced electro-mechanical non-linear model replaces the linear constitutive equations commonly used. Further on, a linear second order model compensates the frequency response of the actuator. Each individual model is fully characterized from experimental data yielded by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…Moreover, Gao et al [131] developed a linear modeling approach for the piezo-actuated stage, where the hysteresis effect of the piezoelectric actuator was ignored. Following the accumulated research results in [129]- [132], Gu et al [20] recently developed a general dynamic model for the piezo-actuated stages, including frequency response of the whole electromechanical system, voltage-charge hysteresis and nonlinear electric behavior. Fig.…”
Section: Comprehensive Dynamic Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Gao et al [131] developed a linear modeling approach for the piezo-actuated stage, where the hysteresis effect of the piezoelectric actuator was ignored. Following the accumulated research results in [129]- [132], Gu et al [20] recently developed a general dynamic model for the piezo-actuated stages, including frequency response of the whole electromechanical system, voltage-charge hysteresis and nonlinear electric behavior. Fig.…”
Section: Comprehensive Dynamic Modelingmentioning
confidence: 99%
“…It is pointed out that the general dynamic model (30) and (31) can be reduced to other developed models in [129]- [132]. The detailed notations and discussions may refer to [20].…”
Section: Comprehensive Dynamic Modelingmentioning
confidence: 99%
“…33 33 Equation (8) indicates that the induced displacement is directly proportional to input voltage when the external load remains constant, and similarly, the external force is proportional to the voltage when the displacement remains constant. Five control voltages (30, 60, 90, 120 and 150V) were selected in the identification process, as shown in Fig.…”
Section: A Coupling Factors Identificationmentioning
confidence: 99%
“…7. This is due to the inherent nonlinearity of coupling factors when the piezoelectric materials are subject to high control voltages [8]- [10]. …”
Section: A Coupling Factors Identificationmentioning
confidence: 99%
“…The electrical properties of these sensors are frequently employed as sensing signals reflecting the stress or strain under external static and or dynamic loadings of the cement concrete matrix which is incorporated with some microscale or nano scale additives, such as carbon fibers (CFs), carbon nanotubes (CNTs) [4][5][6][7][8][9][10], or lead zirconate titanate (PZT) powder [11][12][13][14][15][16]. As Li et al [11,15], Huang et al [12], Chaipanich et al [13], Luo et al [14], Gong et al [16], Lan et al [17], Song et al [18][19][20], and Jaitanong et al [21] reported, the 0-3 type piezoelectric cement-based composite (PCM) wafer has excellent piezoelectric self-sensing and self-driving responses, and a good compatibility with long-life concrete. Therefore, it is easy to realize the fine regulation of performance indicators through changing the fillers' contents [14].…”
Section: Introductionmentioning
confidence: 99%